Advanced Capacity-Expansion-Type Unified Power Flow Controller Based on Single-Core Phase-Shifting Transformer - Ningyu Zhang; Huarui Li; Jicheng Fang; Chongze Bi; Xiaokuan Jin; Jianhua Wang (Energies)
In light of the growing complexity and demand in modern power systems, there is an increasing need for reliable, efficient, and flexible power flow control mechanisms. The Unified Power Flow Controller (UPFC), as a fundamental component of Flexible AC Transmission Systems (FACTSs), has garnered considerable attention due to its exceptional capabilities in regulating power flow and maintaining voltage stability. Nevertheless, the expense associated with high-capacity UPFCs is considerable, thereby rendering their practical implementation challenging. Phase-shifting transformers are less costly but require better power flow characteristics. Therefore, this paper puts forth the proposition of an Advanced Capacity-Expansion-Type Unified Power Flow Controller (ACET-UPFC) based on a single-core phase-shifting transformer (SCPST). This proposed topology is designed to enhance the capacity of the conventional UPFC, while maintaining similar power flow characteristics, and demonstrates strong voltage regulation capabilities, enabling connections across different voltage levels, thereby rendering it more economically feasible for large-scale deployment. This paper presents a detailed analysis of the power flow characteristics of the ACET-UPFC, including a theoretical foundation, mathematical modeling, and an investigation into the impact of various design parameters. Moreover, the ACET-UPFC’s capacity expansion capability and power flow characteristics are also examined. The ACET-UPFC is subjected to further investigation through the use of the PLECS simulation platform, thereby offering a more efficient and cost-effective solution for modern power grids.